Current challenges in the treatment of osteoporosis: an opportunity for bazedoxifene. (June 2014) - Reginster, Jean-Yves; Ferrari, Serge; Hadji, Peyman
Abstract Background: Osteoporosis affects millions of postmenopausal women worldwide. Osteoporosis-related fractures can lead to chronic pain, disability, systemic complications, and increased risk of recurrent fractures, resulting in increased healthcare costs and mortality. Because currently available therapies have unique benefit/risk profiles, challenges remain in selecting the most appropriate treatment for each osteoporotic woman. Research and results: Bazedoxifene (BZA), a new selective estrogen receptor modulator, is being developed for postmenopausal osteoporosis. In a 3 year, global, phase 3 study, BZA significantly reduced the risk of new vertebral fractures and nonvertebral fractures in women with higher baseline fracture risk compared with placebo. In two extensions of this study, the efficacy of BZA in reducing vertebral fracture risk was sustained over 7 years. BZA improved lumbar spine and total hip bone mineral density compared with placebo at 3 and 5 years, and demonstrated a favorable safety/tolerability profile, with no endometrial or breast stimulation. BZA was cost-effective compared with raloxifene in a 3 year, head-to-head comparative trial. Indirect comparisons further suggest that BZA may be as effective as bisphosphonates in reducing risk of nonvertebral fractures in women at high risk of fracture. BZA demonstrated efficacy and safety for treating postmenopausal osteoporosis over 7 years, particularly in women at a higher fracture risk. Conclusion: Because of its specific pharmacologic profile, BZA may be appropriate for postmenopausal women seeking a tolerable, safe, effective, and cost-effective long-term osteoporosis treatment.